2010
DOI: 10.1007/s11274-010-0321-y
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol potential of an endophytic Serratia sp. G3 and its mode of action

Abstract: Biological control is being considered as an alternative or a supplemental way of reducing the use of chemicals in agriculture. An endophytic strain G3 with potential as a biocontrol agent was isolated from the stems of Triticum aestivum L. It was classified by 16S rDNA sequencing as a member of Serratia. Strain G3 displayed a broad spectrum of antifungal activity in vitro against a number of phytopathogens such as Botrytis cinerea, Cryphonectria parasitica, Rhizoctonia cerealis and Valsa sordida. Molecular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 21 publications
(24 reference statements)
0
36
0
Order By: Relevance
“…To determine the impact of SptR on production of exoenzymes and secondary metabolite, firstly proteolytic activities were assayed on skimmed milk agar plates by seeding 2 µl of bacterial overnight cultures onto the plate and monitoring the appearance of haloes around the developing bacterial colonies after 48 h at 28°C as previously described (Liu et al, 2010). Furthermore, overnight cultures of bacteria in LB broth with appropriate antibiotics were diluted (OD600 0.02) into 2 ml of LB with 200 μg/ml of tryptophan.…”
Section: Assays For Proteolytic Activity and Iaa Productionmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine the impact of SptR on production of exoenzymes and secondary metabolite, firstly proteolytic activities were assayed on skimmed milk agar plates by seeding 2 µl of bacterial overnight cultures onto the plate and monitoring the appearance of haloes around the developing bacterial colonies after 48 h at 28°C as previously described (Liu et al, 2010). Furthermore, overnight cultures of bacteria in LB broth with appropriate antibiotics were diluted (OD600 0.02) into 2 ml of LB with 200 μg/ml of tryptophan.…”
Section: Assays For Proteolytic Activity and Iaa Productionmentioning
confidence: 99%
“…To evaluate the effects of SptR in the suppression of pathogenic fungi, strain G3 and the ∆sptR mutant were tested for in vitro antagonistic activity against gray mould Botrytis cinerea as previously described (Liu et al, 2010). Briefly, overnight culture of strain G3 and its derivatives in LB at 28°C were spotted (2 μl) in a line 3 cm away from the centre of the PDA plate, respectively; 5 mm diameter agar disks from an actively growing fungal culture were seeded at the centre of PDA plates (60 mm diameter).…”
Section: Bioassay Of the Antifungal Activity In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…Plant-associated Serratia plymuthica belongs to the group of gamma-proteobacterial species of Gramnegative bacteria as a biocontrol agent (BCA) of mainly fungal pathogens, as well as entomopathogens and weeds. Multiple modes of action and their synergistic effects have been recognized for plant growth promotion and biocontrol (12,13). Previous studies have shown that multiple global regulators including GacS/GacA homologues, GrrA/GrrS, the stationary-phase sigma factor RpoS, and Nacylhomoserine lactone (AHL)-mediated QS system are involved in control of biocontrol activities in S. plymuthica strains IC1270 and HRO-C48 (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%